2014
DOI: 10.21273/horttech.24.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Improving Peer Relations of Elementary School Students through a School Gardening Program

Abstract: For older elementary school students, amicable peer relationships are important to meeting developmental challenges, such as socialization. Thus, in this study, the effectiveness of a school gardening program to promote positive social relationships among elementary school students was assessed. The participants in this study were fifth and sixth grade students from four elementary schools in Wonju, South Korea. The experimental and control groups consisted of 123 students each (total 246) from fifth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Working in a garden with friends, colleagues, or family members also provides an opportunity to improve life skills, such as teamwork, cooperation, accomplishment of goals, self-confidence, self-expression, and the ability to accept the decisions of others (Choi, 2007;Kim, 2006;Song, 2002;Song, 2008;Yoon, 2001). Kim et al (2014) reported that 123 elementary school students experienced improved peer relations, peer stature, and sociality after participating in 10 weekly sessions of gardening intervention. Gardening also provides enjoyment and fun; continuous participation in gardening represents part of a physically active lifestyle.…”
Section: Therapeutic Effects Of Horticultural Activitiesmentioning
confidence: 99%
“…Working in a garden with friends, colleagues, or family members also provides an opportunity to improve life skills, such as teamwork, cooperation, accomplishment of goals, self-confidence, self-expression, and the ability to accept the decisions of others (Choi, 2007;Kim, 2006;Song, 2002;Song, 2008;Yoon, 2001). Kim et al (2014) reported that 123 elementary school students experienced improved peer relations, peer stature, and sociality after participating in 10 weekly sessions of gardening intervention. Gardening also provides enjoyment and fun; continuous participation in gardening represents part of a physically active lifestyle.…”
Section: Therapeutic Effects Of Horticultural Activitiesmentioning
confidence: 99%
“…Children's experiences in gardens or in observing the plant growth process in cooperation with their peers provide opportunities for emotional development (Kim et al, 2014). Working cooperatively with plants in gardens provides children with various emotional experiences and opportunities to understand others' feelings.…”
Section: Items Zmentioning
confidence: 99%
“…A study by Hwang (2004) of a 10-week gardening program showed significant improvements in helping, sharing, and cooperation skills among children aged 4 to 5 years. Kim et al (2014) reported that elementary school children improved in the areas of persistence and adaptability within peer relationships, as well as compliance with classroom rules and collaboration with classmates by participating in a school gardening program. Waliczek et al (2001) reported that school gardens had positive effects on Table 5.…”
Section: Items Zmentioning
confidence: 99%
“…Another study reported improved parent self-efficacy and self-esteem and mitigated parenting stress among mothers who participated in a six-week care farming program, as compared to a control group [28]. In other studies, children were found to have improved overall health outcomes, including physical and physiological (e.g., physical activity and cortisol levels), psychological (e.g., emotional intelligence, eco-friendly attitude, and self-esteem), cognitive (e.g., attention and concentration, and creativity), social (e.g., peer relationships and social ability), educational (e.g., scientific attitude and exploration ability), and behavioral (e.g., dietary habits) improvements [24,[29][30][31][32][33][34][35][36][37][38]. However, most studies conducted to date have only explored the effects of care farming programs for individuals such as adult women or children, and have not focused on the relationships or interactions between family members within a family care farming program.…”
Section: Introductionmentioning
confidence: 99%